(untitled) (Global Scientific Review, 2026)
Cardiovascular diseases (CVD) are one of the leading causes of death worldwide, and a healthy lifestyle plays a crucial role in their prevention. This article analyzes the impact of healthy habits such as nutrition, physical activity, smoking cessation, weight control, sleep, and stress management in preventing CVD. Research indicates that by adhering to a healthy lifestyle, 80-90% of CVD cases can be prevented. The article provides recommendations based on the World Health Organization (WHO), the American Heart Association (AHA), and other scientific sources. Furthermore, the effectiveness of these habits is proven through clinical studies and statistical data. Consequently, the role of physicians and society in promoting a healthy lifestyle is highlighted. The article aims to strengthen CVD prevention, with a total word count of approximately 2,400.